Management quality and the cost of debt: Does management matter to lenders? - Rahaman, Mohammad M.; Zaman, Ashraf Al (Journal of Banking & Finance, 2013)
This paper investigates the effect of organizational capital, typified by various management practices within a firm, on the cost of external debt financing. Using a sample of medium-sized manufacturing firms in the US, we find that better management practices enhance a firm’s external financing capacity by lowering the firm’s cost of bank loans. We do not find any evidence that the lower loan cost of a high-quality-management firm is associated with more restrictive non-price contract terms such as greater collateral requirements and stricter covenants. These results suggest that banks explicitly take into account the risk arising from poor management practices when pricing and designing debt contracts.